Reconstructing School and Madrasah Management through the Integration of Values, Transformational Leadership, and Curriculum Innovation - Ilyas; Nispi Syahbani (Al-Qalam Institue, 2025)
This study aims to examine the reconstruction of school and madrasah management through the integration of foundational values, the implementation of transformational leadership, and the advancement of curriculum innovation within the framework of 21st-century education. Employing an integrative literature review methodology, the study systematically analyzes 45 reputable scholarly publications published between 2019 and 2024. Literature selection was conducted through comprehensive searches in national and international academic databases, guided by criteria of thematic relevance, methodological rigor, and theoretical contribution. The findings underscore that the substantive reconstruction of educational management necessitates the synergy of three core dimensions: first, the internalization of character and spiritual values as the foundation for an ethical and visionary organizational culture; second, the paradigm shift in leadership from authoritarian-directive models to collaborative, inspirational, and empowering approaches; and third, curriculum innovation that is responsive to global challenges, local needs, and technological developments. The integration of these elements cultivates a dynamic, inclusive, and sustainable educational ecosystem. This study provides valuable insights for educational policymakers and leaders, suggesting that a holistic approach to school and madrasah management—anchored in character values, transformational leadership, and curriculum innovation—can drive sustainable improvements in educational outcomes.